Use of social networks sites (SNS), career success and information power - Wok, Saodah; Hashim, Junaidah; Juhdi, Nurita (2013)
This study aims to examine the relationship between the use of social network sites and career success. It further examines whether this relationship is mediated by information power of the networkers. This study used primary data collected from 308 employees of various sizes of organisation in Malaysia. The findings revealed that there is no relationship between the studied variables and information power does not mediate the relationship. The implications of the study are discussed.